Screening and characterization of ligninolytic fungus from mixed organic matter - Lobo, Rodab (Universiti Malaysia Sarawak (UNIMAS), 2007)
Three difference types of mixed organic matter from agriculture's wastes have led to successful isolation of 24 indigenous fungal isolates. Among these isolates, Aspergillus sydowii strain NRRL 250 (OP11), Pestalotiopsis theae isolate P145 (PA6) and Cladosporium cladosporioides strain Hu01 (PA21) were further selected for lignin degradation analysis, where all three isolates have consistent ligninolytic enzymes activities for all four enzymes tested earlier in minimal media. PA21 also show active Congo Red dye degradation activity as compared to other four difference species all positive for the test. PA21 was the best Lignin peroxidase (LiP) and laccase producing fungi. Cellulase is the highest enzyme secreted for all fungal isolates. Enzyme activities ranged from 44.16-337.87 U/mL (LiP), 1.55-50.03 U/mL (laccase), 23.43-276.64 U/mL (MnP), and 184.0-1449.0 U/mL (cellulase). Highest enzyme activities for LiP and cellulase achieved by isolate OP11 on day 11, while for Manganese peroxidase (MnP) achieved by isolate PA6 on day 5 and for laccase by isolate PA21 on day 5.